Comparative analysis of the level of physical health of students of economics specialties - Salatenko I.O (Kharkov National Pedagogical University, 2013)
The results of the study of the level of physical health of students of economics specialties were conducted. The study involved 636 students. It was used the method of assessing the level of physical health G.L. Apanasenko. Defined by the functional state of the organism in terms of cardio-respiratory and muscular systems, which are formalized in quantitative terms (points) and are associated with the level of individual health. It was stated that the vast majority of students have low rates with the steady tendency to deterioration over the period of study. Found that physical education classes do not fulfill the full recreational function. Self-improvement gives little impact or affect the health of students. The necessity of developing the content of a sports-oriented technology of physical education students on the basis of volleyball and aimed at improving the professional-applied physical fitness.